The effect of different percentages of kenaf on the mechanical properties of adobe - Ahmed Alburaiki, Abdulaziz Salem (2019)
Soil is the oldest and largest source of structures on since long time, Statistics show that about nearly 30% of the Earths still inhabitants live in mud buildings, particularly in rural areas and cities located in the ancient archaeological plains and valleys surrounded by vast plains, 50% represents a civilized nation. Earth climatic economic environment-friendly is used in a broad and large-scale construction around the world, especially in those countries that not possess large plant life on its territory. The use of the soil before ten thousand years as a major source for the building, along with stones and still some of the remnant of those buildings found until now. In this study, adobe with different proportions of Kenaf. Meanwhile, the control is pure adobe which does not have Kenaf. In addition, different proportions of Kenaf are 0.25%0.5% and 0.75%. There are two types of tests conducted, compressive strength test and flexural strength test. All the specimens were 7 days in air then 7 days in Ventilated Oven with T= 40 C.